2012
DOI: 10.1111/j.1445-2197.2012.06238.x
|View full text |Cite
|
Sign up to set email alerts
|

Different approaches to volume assessment of lymph nodes in computer tomography scans of head and neck squamous cell carcinoma in comparison with a real gold standard

Abstract: The data show a higher reliability for volumes estimated by the segmentation-based approach than the widely used diameter-based approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…For LN algorithm development, 2D approaches have been published based on the measurement of the axial SAD as used in the classification systems mentioned above [ 29 , 30 ]. However, Mueller et al [ 31 ] found that in the head and neck region, the 2D segmentation method tends to overestimate the LN volume. Using a 3D approach based on the perimeter, they found a closer correlation to the true LN volume determined after neck dissection.…”
Section: Discussionmentioning
confidence: 99%
“…For LN algorithm development, 2D approaches have been published based on the measurement of the axial SAD as used in the classification systems mentioned above [ 29 , 30 ]. However, Mueller et al [ 31 ] found that in the head and neck region, the 2D segmentation method tends to overestimate the LN volume. Using a 3D approach based on the perimeter, they found a closer correlation to the true LN volume determined after neck dissection.…”
Section: Discussionmentioning
confidence: 99%
“…The inherent technical difficulty also results in a threshold of 'minimally measurable disease', below which early stage patients cannot be reliably assessed and may not therefore be treated or offered entry to trials. 7 Volumetric tumour measurement is established in lung 8 and other cancers [9][10][11] and eliminates decision-making about where to make, and how to replicate, unidimensional measures on serial scans. Volumetric measurements based on MRI have recently been shown to outperform traditional T-staging in predicting survival, 12 but MRI is not available routinely and CT remains the primary imaging modality used in MPM.…”
Section: Pleural Diseasementioning
confidence: 99%
“…Volumetric tumour measurement is established in lung8 and other cancers9–11 and eliminates decision-making about where to make, and how to replicate, unidimensional measures on serial scans. Volumetric measurements based on MRI have recently been shown to outperform traditional T-staging in predicting survival,12 but MRI is not available routinely and CT remains the primary imaging modality used in MPM.…”
Section: Introductionmentioning
confidence: 99%
“…Because it can be assumed that the volume of cancer reflects the number of cancer cells, the tumor volume should influence the production of mNS and the amount excreted and appearing in urine. Since the TNM categories (13) of the patients with HNSCC were available and some of the HNSCC in an accompanying study underwent volume assessment via computed tomography-based volumetry via image segmentation (14), the total volume of the malignant lesions was calculated after estimation of the volumes of the primary HNSCC (T) and potentially present locoregional lymph node metastases (N) and distant metastases (M).…”
Section: Determination Of Mnsmentioning
confidence: 99%